2021
DOI: 10.1007/s13300-021-01025-x
|View full text |Cite
|
Sign up to set email alerts
|

Ten-Year Outcomes of Percutaneous Coronary Intervention Versus Coronary Artery Bypass Grafting for Patients with Type 2 Diabetes Mellitus Suffering from Left Main Coronary Disease: A Meta-Analysis

Abstract: Introduction In this meta-analysis, we aimed to systematically compare the 10-year outcomes of percutaneous coronary intervention (PCI) versus coronary artery bypass grafting (CABG) in patients with type 2 diabetes mellitus (T2DM) suffering from left main coronary artery disease (LMCD). Methods Medical Literature Analysis and Retrieval System Online (MEDLINE), http://www.ClinicalTrials.gov , Excerpta Medica dataBASE (EMBASE), Cochrane Central,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
13
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 32 publications
1
13
0
Order By: Relevance
“…The SYNTAX score can assist in guiding the choice of reasonable revascularization in patients with three branches lesions or left main artery lesions. The higher the SYNTAX score, the worse the short-term clinical outcome after PCI ( 16 , 17 ). Wang reported that a study of 2,348 patients with congenital heart disease (CHD) and the SYNTAX score were performed for all enrolled patients before PCI, and then divided into high-risk group, medium-risk group, and low-risk group.…”
Section: Discussionmentioning
confidence: 99%
“…The SYNTAX score can assist in guiding the choice of reasonable revascularization in patients with three branches lesions or left main artery lesions. The higher the SYNTAX score, the worse the short-term clinical outcome after PCI ( 16 , 17 ). Wang reported that a study of 2,348 patients with congenital heart disease (CHD) and the SYNTAX score were performed for all enrolled patients before PCI, and then divided into high-risk group, medium-risk group, and low-risk group.…”
Section: Discussionmentioning
confidence: 99%
“…Even with multivariable analyses and statistical adjustment, these studies may be subject to residual confounding, as patients referred for CABG in a clinical (or nonrandomized) setting are fundamentally different than those referred for PCI. Meta‐analyses including observational studies are subject to similar biases 10,11 …”
Section: Discussionmentioning
confidence: 99%
“…Although the mortality of CAD has been well-controlled with the development of interventional strategies, the prognosis of patients with CAD and T2DM is still very poor [26]. The CAD and T2DM patients are prone to a more rapid progression of atherosclerosis, significantly increasing the need for myocardial revascularization [27]. Besides, patients with T2DM also have a worse prognosis following a coronary revascularization procedure [28].…”
Section: Discussionmentioning
confidence: 99%